MODEL PENDANAAN ARMADA KAPAL NASIONAL FUNDING MODEL of NATIONAL SHIP ARMADA - Ridwan, Mohd (TEKNIK, 2008)
Domination of Foreign ship armada in trading activity of exsport/import and interisland in Indonesia,couse deficit state 99 trilium rupiah per year. The national shipping armada can not serve sea transportto support commercial activity. They have not provides enough ship armada capacity for tradingcommodity, and dosent enaugh funding development of new ship armada, so that national armada freightcapacity always downwards along increasingly ship age. Economic from transportation sector of seawhich capital intensive, labour intensive and high tech, requires a policy of government which insubvention with funding especially from banking sector and finance companies non bank. It is requiredmodel or funding pattern which to support the sector, expected later national ship armada can transportall commerce commodity of exsport/import and interisland in country